NILAI-NILAI BUDAYA PARA TOKOH UTAMA DALAM NOVEL KEMBARA RINDU KARYA HABIBURRAHMAN EL-SHIRAZY: KAJIAN SOSIOLOGI SASTRA - Fatimah Fatimah (Academica: Journal of Multidisciplinary Studies, 2021)
Habiburrahman's novel Kembara Rindu is the first soul-building dwilogi novel written by Habiburrahman El Shirazy. This novel portrays Lampung's cultural life and pesantren by instilling the cultural values of the main characters in the novel. This study aims to describe the forms and inculcation of the cultural values of the main characters. The data source of this research is from the novel Kembara Rindu by Habiburrahman El Shirazy. The research method used is qualitative method. Data collected in the form of words and sentences taken from the novel Kembara Rindu. The data collection technique used is listening and note taking. The results of the study are the inculcation of the cultural values of the main characters found in the novel Kembara Rindu by Habiburrahman El-Shirazy namely there are three instillations of cultural values. First, the inculcation of the cultural values of the main characters towards God. Second, the inculcation of the cultural values of the main characters in themselves or as individual beings. Third, the inculcation of the cultural values of the main characters towards other human beings or as social creatures. This research can be applied in everyday life as an inculcation of good attitudes and morals in order to create peace in life with Islamic teachings that are not dogmatic.Keywords: cultural values; novels; sociology of literature